(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Being one of the fastest growing industries in the world Islamic banking system attracts entrepreneurs with its fairness and no interest rate. Spreading not only in Muslim countries, but in Europe and the USA, it finances production projects that are safe for society as permitted by Sharia. In the article advantages and disadvantages of Islamic and traditional banking system, SWOT analyses were illustrated. The specific feature of the article is that it gives clear picture of financial situation of Central Asian countries, as well as, the Republic of Uzbekistan. The basic principles of Islamic banking are identified, on the basis of which the criteria for distinguishing between Islamic and traditional investment banking products are substantiated. Substantiated recommendations for the introduction of Islamic investment banking products in our banking practice on the basis of: ‒ development of hybrid investment products; ‒ modifications of variants of organizational structures of Islamic banks. Directions for improving the legislative environment for the introduction of investment products of Islamic banking into our banking practice are proposed based on a phased approach to the implementation of its principles and taking into account the factors that determine the volume and sequence of passing through these stages.